Fiscal transfers in the spatial economy - Marcel Henkel; Tobias Seidel; Jens Südekum (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2019)
Many countries shift substantial public resources across jurisdictions to mitigate spatial economic disparities. We use a general equilibrium model with multiple asymmetric regions, labor mobility, and costly trade to carve out the aggregate implications of fiscal transfers. Calibrating the model for Germany, we find that transfers indeed deliver smaller disparities across regions. This comes at the cost of lower national output, however, because activity is diverted away from core cities and towards remote areas with low productivity. But despite this output loss, national welfare may still increase, because the transfer scheme countervails over-congestion in large cities.
Keywords: F15; R12; R13; R23; 330; fiscal equalization; regional transfers; migration; spatial economics